2012
DOI: 10.1021/mz300458x
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Sulfites: Efficient Reducing Agents and Supplemental Activators for Atom Transfer Radical Polymerization

Abstract: Inorganic sulfites such as sodium dithionite (Na 2 S 2 O 4 ), sodium metabisulfite (Na 2 S 2 O 5 ), and sodium bisulfite (NaHSO 3 ) have been studied as reducing agents for atom transfer radical polymerization (ATRP). They act not only as very efficient reducing agents but also as supplemental activators for SARA (supplemental activator and reducing agent) ATRP of methyl acrylate in DMSO at ambient temperature. In combination with Cu(II)Br 2 /Me 6 TREN, they produced poly(methyl acrylate) with controlled molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 38 publications
3
92
0
Order By: Relevance
“…However, in the past decade several new methods were developed that provide well-controlled polymerizations, in the presence of ppm amounts of Cu catalyst and various reducing agents (72,73). These reducing agents continuously regenerate the activator complex and compensate for radical termination (74)(75)(76). In continuous activator regeneration (ICAR) ATRP these processes employ the same radical initiators as in RAFT (23), whereas in electrochemically mediated ATRP (77), or photochemically mediated ATRP no initiator based chains are formed (78)(79)(80)(81).…”
Section: Crp In the Presence Of Cumentioning
confidence: 99%
“…However, in the past decade several new methods were developed that provide well-controlled polymerizations, in the presence of ppm amounts of Cu catalyst and various reducing agents (72,73). These reducing agents continuously regenerate the activator complex and compensate for radical termination (74)(75)(76). In continuous activator regeneration (ICAR) ATRP these processes employ the same radical initiators as in RAFT (23), whereas in electrochemically mediated ATRP (77), or photochemically mediated ATRP no initiator based chains are formed (78)(79)(80)(81).…”
Section: Crp In the Presence Of Cumentioning
confidence: 99%
“…Dimanganese decacarbonyl (Mn 2 (CO) 10 ) has a weak Mn-Mn linkage and visible light photolysis provides the • Mn(CO) 5 metalloradicals which are not capable of initiating polymerization but abstracting halides from a variety of organohalogen compounds, generating the corresponding carbon centered radicals (Scheme 3). We have previously shown that manganese based radical generation process can successfully be employed in different modes of polymerization processes including radical promoted cationic polymerization (51), mechanistic transformation (52,53), radical coupling (54), hyper-branching (55) and grafting from polyolefines (56).…”
Section: Visible Light-induced Atrp By Using Dimanganese Decacarbonylmentioning
confidence: 99%
“…Copper and iron compounds are particularly successful metal catalysts used in ATRP, but there are also studies reporting other transitional metals such as ruthenium, molybdenum and osmium (5). During the past years, various initiation techniques involving simultaneous reverse and normal initiated (SR&NI), activators by electron transfer (AGET), activators regenerated by electron transfer (ARGET) (6), initiators for continuous activator regeneration (ICAR) (7,8), and supplementary activator and reducing agent (SARA) ATRP (9,10), and single electron transfer-living radical polymerization (SET-LRP) have been reported to create some substantial benefits for environmental and practical issues, i.e. in the presence of oxygen, at room temperature or the use of catalyst at the level of parts per million (ppm).…”
Section: Introductionmentioning
confidence: 99%
“…In the initiators for continuous activator regeneration ATRP process (ICAR ATRP), conventional radical initiators are being used . The "supplemental activators and reducing agents ATRP" process (SARA ATRP) is based on zerovalent metals (Abreu et al 2012). Electrochemistry, that can be run under either potentiostatic or galvanostatic conditions, is used in electrochemical ATRP (eATRP; Magenau et al 2011).…”
Section: Surface Modification By Surface-initiated Atom Transfer Contmentioning
confidence: 99%